Comparison of Compressive Strength of Concrete Using White Portland Cement with Gray Cement - Ginting, Arusmalem; Pradikta, Damar Hendra; Santosa, Bing; Adi, Prasetya (Universitas Negeri Semarang, 2022)
Abstract. White Portland cement (WPC) in Indonesia is generally used for architectural work. WPC is still rarely used in structural concrete because the price is relatively higher than grey cement. This research reviewed the compressive strength of concrete using WPC and compared it with concrete using grey cement. Compressive strength testing of concrete using WPC and grey cement was carried out at ages: 3, 7, 14, 21, and 28 days. From the research, the compressive strength of concrete using WPC was 13.81 MPa (60%) at 3 days, 16.68 MPa (72%) at 7 days, 19.45 MPa (84%) at 14 days, 22.34 MPa (97%) at 21 days, and 23.11 MPa (100%) at 28 days. The compressive strength of concrete using grey cement was 13.03 MPa (63%) at 3 days, 15.11 MPa (74%) at 7 days, 17.22 MPa (84%) at 14 days, 18.78 MPa (91%) at 21 days, and 20.54 MPa (100%) at 28 days. The compressive strength of concrete using WPC is higher than grey cement at all ages. The rate of compressive strength of concrete using WPC is almost the same as grey cement at all ages.